The role of chest ultrasound in diagnosing invasive fungal infections in acute leukemia patients - Ana-Maria NEAGU; Ana-Maria VLĂDĂREANU; Horia BUMBEA; Diana CÎŞLEANU; Cristina CIUFU; Cristina MARINESCU; Minodora ONISÂI; Mihaela GĂMAN (Romanian Journal of Medical Practice, 2016)
Acute leukemia patients are the category of highest risk to develop invasive fungal infections, have high morbidity and mortality rates related to these complications. The diagnosis of these infections must be accurate and early. That is the main reason for searching non-invasive, fast, available and low cost diagnostic methods. Imagistic diagnosis is essential, computer tomography is the gold standard. Chest ultrasound has most of these characteristics, offers valuable informations and they are accurate when compared to the chest tomography results. The decision to initiate antifungal therapy is significantly better than the empirical therapy, having lower mortality rate among these patients.